Emerging Sustainable Energy Technologies to Combat Climate Change: Evidence using Non-linear ARDL Estimation - Sadiq, Muhammad; Aldeehani, Talla M; Salman, Syed Muhammad; Riaz, Samina; Khan, Aisha (Transformations In Business & Economics, 2025)
Economies, either developed or developing, face problems in the form of climatic issues as they fail to restrict greenhouse gas emissions. The challenge increases as these emissions are due to high levels of consumption of non-renewable energy. Thus, in order to mitigate emissions, especially CO2, it is imperative to enhance the green energy share of the energy supply. Interestingly, scholars agree that public sector investment to raise renewable energy is significant, hence they hypothesize that investment is crucial for the technological advancement needed to increase sustainable energy production and supply. The circumstantial role of sustainable technology cannot be overlooked, as it boosts green energy supply and protects the environment.  Because of climate complexities and rapid urbanization, a zero-carbon economy is not easy to achieve. To address the issues, countries must find effective ways to restrict carbon emissions, which is only possible if they are aware of the potential determinants of carbon emissions. Based on refined indicators, this study presents a comprehensive model to quantify the role of sustainable energy technologies in climate change in the context of China between 1991 and 2020. Through autoregressive distributed lag estimations, it reveals that renewable energy consumption and production, along with advanced technologies, are blessings for an economy trying to reduce carbon emissions. However, economic activity, rapid urbanization and industrial structures are responsible for high emissions. The findings suggest that certain target policies must be implemented to reduce carbon emissions. Also, there should be a proper platform to promote green technology at a regional level along with effective urban development strategies.
Keywords: sustainable energy technologies; renewable energy production; technology adoption; CO2 emissions; urbanization; industrialization; zero carbon economy